A review of improvements in the utilization of low-grade Turkish lignitic coals for environmental considerations - M. Kaya (School of Industrial Technology, Universiti Sains Malaysia, 2014)
This review concentrates on solving environment problems caused by Tuncbilek lignites and summarizes recent papers for improving coal quality and recovering unburned carbonaceous matter (UCM) from the bottom ashes by flotation. Settling behavior of coal fines was also investigated. The effects of operating variables on mechanical flotation performance of ron-of-mine and -0.5 mm coals were determined. Separation of UCM from the bottom ash of Tuncbilek Power Plant (TPP) using Jameson cell and column flotation was carried out. Tuncbilek lignites favorably to mechanical flotation with recoveries in excess of 95% using both kerosene and dodecylamine (DDA) at 14% ash content. Kerosene, DDA and pH have positive effects on recovery. The effect of DDA was greater than kerosene, but its selectivity for ash reduction was insignificant. The -0.5 mm Tuncbilek coal was also floated by mechanical flotation at a 62% combustible recovery. Optimum operating parameters were -0.200 mm size, pH 10, 15% solid, 1 kg/t kerosene, 0.2 kg/t MlBC, 6 l/min airflow rate and 1000 rpm. Ash content decreased from 32.3% to 22.1%, combustible S from 1.52% to 0.91%, S%/kcal 0.34& to 0.193 and lower calorific value (LCV) increased from 3962 to 4687 kcal/kg. Sedimentation of Tuncbilek fines was improved by Ca ions in the presence polymeric flocculent (HF7170). Oleic acid and K-oleate also improved the settling behavior of fines with CA ions. The aggregation of particles is aided by Ca ions is also linked to reduction of negative surface charge. UCM are separated from the bottom ash with a recovery of 67.5% at ash content of 44%, using a Jameson cell. LCV of the product was 3740 kcal/kg, which could be useful as a recycled energy. Column flotation of the same bottom ashes for the unburned coal was achieved at 42.6% ash and 53.8% combustible recovery. LCV increased from 1270 ο 3840 kcal/kg.